2016
DOI: 10.1007/s10144-016-0554-1
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of the direct and indirect effects of endemic seaweeds, barnacles, and invertebrate predators on the abundance of the introduced rocky intertidal barnacle Balanus glandula

Abstract: The barnacle, Balanus glandula has recently invaded along the Pacific coast of eastern Hokkaido, Japan. To evaluate the direct and indirect effects of endemic seaweeds, barnacles, and invertebrate predators on the abundance of B. glandula on the rocky intertidal coast of eastern Hokkaido, we conducted a field experiment from June 2011 to October 2012 in which we manipulated the presence or absence of these factors. Seaweeds showed no significant effect on the abundance of B. glandula. The endemic barnacle Chth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Additionally, dogwhelk nonconsumptive effects, which are mediated through mucus-released chemical cues indicative of predation risk by dogwhelks (Johnston & Strathmann, 1989), limit B. glandula recruitment (Yorisue, Ellrich & Momota, 2019). Moreover, substrate pre-emption by C. dalli adults limits B. glandula abundance (Alam & Noda, 2016). However, our results show that C. dalli and B. glandula recruit density were not correlated, indicating that there are no interactions between C. dalli and B. glandula recruits under the examined recruit densities.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Additionally, dogwhelk nonconsumptive effects, which are mediated through mucus-released chemical cues indicative of predation risk by dogwhelks (Johnston & Strathmann, 1989), limit B. glandula recruitment (Yorisue, Ellrich & Momota, 2019). Moreover, substrate pre-emption by C. dalli adults limits B. glandula abundance (Alam & Noda, 2016). However, our results show that C. dalli and B. glandula recruit density were not correlated, indicating that there are no interactions between C. dalli and B. glandula recruits under the examined recruit densities.…”
Section: Discussioncontrasting
confidence: 67%
“…Understanding biotic resistance is a central goal of invasion biology (Stachowicz et al, 2002;Kimbro, Cheng & Grosholz, 2013). Recent research from Hokkaido revealed that native dogwhelks (Nucella lima) limit B. glandula abundance (Alam & Noda, 2016) and thus contribute to biotic resistance against B. glandula. These predatory snails prefer B. glandula as prey over C. dalli (Yorisue, Ellrich & Momota, 2019), likely as B. glandula is more nutritious (Palmer, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases such effects may be relatively predictable (e.g. a dense algal canopy can provide shelter from desiccation and refuge from predators, Moore et al ., 2007), but sometimes relatively subtle differences in the abundance of one species can have dramatic and often unpredictable indirect effects on the behaviour and abundance of another species (Anderson, 1999; Trussell et al ., 2006; O'Connor et al ., 2013; Rashidul Alam & Noda, 2016). Moreover, the costs and benefits of activity out of the shelter are variable in both time and space, and to maximize benefits and minimize risk at any given time it is important for an organism to be able to react to locally changing conditions and modify its behaviour.…”
Section: Introductionmentioning
confidence: 99%